Pendampingan Penanaman Nilai Pesantren untuk Pembentukan Karakter Santri di Pondok Tahfidz Arabic Al-Gontory Malaysia - Vina Fithriana Wibisono; Syamsuri; Suyoto Arief; Nadhilah (Athallah Publishing Globalndo, 2026)
Globalization and modernization have posed serious challenges to the character development of students, particularly children and adolescents. This condition highlights the need for strengthening character education that is not merely cognitive but also practical and sustainable. This Community Service Program (PkM) aimed to build students’ character through the internalization of pesantren values, particularly the core values of Panca Jiwa Pesantren, at Tahfidz Arabic Al-Gontory Banin Islamic Boarding School, Bukit Hijau, Rembau, Malaysia. The program employed a community engagement approach through intensive mentoring activities, including Islamic studies sessions, regular lectures, workshops, habituation of daily pesantren activities, and active involvement of students and teachers throughout the program. The participants consisted of students aged 8–15 years and pesantren educators. The results demonstrated positive changes in students’ attitudes and behavior, reflected in increased religious awareness, the practice of a simple lifestyle, the development of self-reliance, strengthened Islamic brotherhood, and the growth of students’ interests and talents in a more directed and responsible manner. This program concludes that the internalization of pesantren values based on Panca Jiwa is effective as a character education model in a tahfidz Islamic boarding school environment and has the potential to be implemented in similar Islamic educational institutions, particularly in international contexts